EFEK LARVISIDAL EKSTRAK ETANOL DAUN KEMANGI (Ocimumsanctum Linn) TERHADAP LARVA INSTAR III Culexquinquefasciatus - LA, Wijayani; S, Isti’anah (Universitas Muhamadiyah Surakarta, 2014)
Filariasis carried by mosquito Culex quinquefasciatus. Filariasis cause elephantiasis sequelae that often lower the sufferers productivity . Eradication of the disease is difficult, then , an attempt to do is to control the vector. The other way is to use insecticide vector control plant. Basil (Ocimum sanctum Linn) which contain fiavonoids, saponins, and eugenol has been shown in the laboratory have larvicidal effect. This study aimed to determine the larvicidal effects from Ethanol extract 96% of basilleaf (Ocimum sanctum Linn) against third instar larvae of Culex quinquefasciatus. This is an laboratory experimental methods with Post test only control group design. The Ethanol extract of basil leaf (Ocimum sanctum Linn) diluted to a concentration of 5000 ppm, 4500 ppm, 4000 ppm, 3500 ppm, 3000 ppm, 2000 ppm, 1500 ppm, 1000 ppm. The experiments were repeated three times. Each experiment included a control ie Tween 20 of 0.25% in distilled water. Statistical analysis was performed with Kruskal-Walls test and probit analysis to determine LC50 and LC90. In the analysis result of Kruskal Walls (CI: 95%) it obtained the results that each test group had a significant difference (p=0,005) in mortality of third instar larvae of Culex quinquefasciatus.The results of probit analysis showed that the ethanol extract of basil leaf give the concentration LC50 and LC90 2281.931 ppm and 5016.314 ppm. Ethanol extract 96% of basilleaf (Ocimum sanctum Linn) has an larvicidal effect on third instar larvae of Culex quinquefasciatus.Keywords: Culex quinquefasciatus - larvicidal - ethanol extract - Basilleaf (Ocimum sanctum Linn).